Analysis Security of Absence Information System with Finger Print using Minutiae Method on STEKOM - Sofyan Laksamana Haidar, Laksamana Rajendra Haidar; Ihsanil Huda, Haris; Sudirman, Bagus (LPPM Universitas Sains dan Teknologi Komputer, 2022)
Employee attendance is primary factor at an institution or company in achieving target. This condition relates to disciplines. And affect to pros and cons company management or human resource quality it self, impact that happened can be in the form of lack of output from production result. Much company managements take decision by conduct salary amputation of each absence employee in the operation. In consequence, must existence of special record to note existence and employees absence in order to employees existence in conducting job activity are noted properly. A lot of way of used for processing employees attendance, one of that is with use barcode machine. In STEKOM, absence system which used is fingerprint scanner machine, but the system mentioned is requiring expensive cost enough, it needs troubleshooting and also repairing. So that company have to releasing a lot of cost for handle employees attendance process. Beside that, damage fingerprint condition, wet and dirty can be became of employees. So its disturb process of absence transaction. Minutiae method is a method which is used by the writer in this research. This method is assumed as an effective method to describe the intrinsic elements in designing and identifying finger print. It is because in processing a program, it should be described in order to be understandable.